A Education Integrating Communicative Competence and Digital Literacy in Arabic Curriculum - Muzakki Abdurrahman; Nur Aqila; Muhammad Thohir (Assuthur: Jurnal Pendidikan Bahasa Arab, 2026)
The development of Arabic language curricula in higher education faces challenges in integrating communicative competence and digital literacy in ways that align with the demands of the 21st century. This study aims to formulate an integrative curriculum model that combines these two aspects in Arabic language learning at Kiai Abdullah Faqih University (UNKAFA) Gresik. The research employs a qualitative approach with a developmental research design, involving 30 students as research subjects and 5 key informants in in-depth interviews. Data were collected through interviews, observations, and document analysis and were analyzed using thematic analysis techniques. The findings indicate that learning is still dominated by a structural approach and that the integration of digital literacy has not yet been carried out systematically. Based on these findings, this study contributes an integrative curriculum framework linking communicative competence and digital literacy for Arabic curriculum development. Therefore, an integrative curriculum model based on communicative competence and digital literacy is proposed through activity- and technology-based learning approaches. This model is expected to enhance students’ communication skills and strengthen their readiness to respond to digital challenges in the global era.